SEA HORSE POPULATION MONITORING IN COASTAL WATERS OF PADANG BAI KARANGASEM BALI - Suprabadevi Ayumayasari Saraswati; Dewa Ayu Angga Pebriani (Samakia : Jurnal Ilmu Perikanan, 2016)
Knowledge of the population biology of natural and Sea Horse was not known by the experts. The scarcity of information makes it difficult to guess the impact of the exploitation of the population Seahorse. As a result of the global demand for Seahorse increasing as well as the uncertainty of the impact of the exploitation of natural populations, the Sea Horse Population monitoring needs to be done. This study was conducted to determine the population Seahorse (Hippocampus sp.) Including the type genus and water quality in its waters. This research was conducted in the waters of Padang Bai Beach Karangasem Bali. This study was conducted from April to June 2016. The determination of the research station is done by purposive sampling technique. For data retrieval Seahorse (Hippocampus sp.) Using the method of least square with a size of 10x10 m in each sampling location. The results were obtained three species of the genus Hippocampus Sea Horse horse. Measurement of physical-chemical parameters such as water temperature, salinity, pH and DO linked to the quality standard Kep.Men.LH 51 about the quality of the waters for marine life is quite good for the presence of Sea Horse.